Systematic Literature Review: Branches of Philosophy and Schools of Thought in Philosophy - Yadi, Supri; Sari, Ice Linsa; Septemi, Yulia; Helita, Helita; Elesti, Yesmi (PPSDP International Journal of Education, 2025)
This study aims to identify, classify, and synthesize the development of branches and schools of thought in philosophy based on the latest academic literature. The method used in this study is a Systematic Literature Review (SLR) with data search through the Google Scholar database using keywords such as schools of philosophy, branches of philosophy, and philosophy. Inclusion criteria included articles in English and Indonesian published between 2021 and 2025 that contain conceptual discussions of branches or schools of philosophy, while exclusion criteria included non-academic articles and popular works. Of the initial 200 articles, 15 studies met the criteria and were synthesized thematically. The results show five main branches (metaphysics, epistemology, ethics, logic, and aesthetics) and seven dominant schools (realism, idealism, pragmatism, existentialism, positivism, phenomenology, and postmodernism). The novelty of the study lies in the systematic mapping of the relationships between branches and schools. Its practical implications strengthen the foundation of the modern philosophy curriculum, while its contribution enriches epistemological understanding in contemporary philosophical studies.